2018
DOI: 10.1002/ccd.27952
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Tryton‐dedicated bifurcation stent for the treatment of true coronary bifurcations: Individual‐patient‐data pooled analysis

Abstract: Objectives We aimed to evaluate the safety and efficacy of the dedicated Tryton side branch (SB) stent for the treatment of true bifurcations involving large SBs. Background Bifurcation lesions are associated with lower procedural success and a higher risk of adverse cardiac events. Provisional stenting (PS) is currently the default approach for the treatment of bifurcation lesions. The Tryton stent is a dedicated bifurcation stent system for the treatment of true bifurcation lesions. Methods We performed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Dedicated bifurcation stents were proposed as one of the resolutions to these issues [ 3 ]. However, few of them have been tested in large randomized clinical trials [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated bifurcation stents were proposed as one of the resolutions to these issues [ 3 ]. However, few of them have been tested in large randomized clinical trials [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This stent is implanted in the SB, and a DES is implanted in the MV through the open struts of this dedicated stent. A pooled analysis of the Tryton pivotal randomized controlled trial and post-approval confirmatory study comparing this stent with the PST with a DES showed that the Tryton stent was clinically non-inferior to the PST with good angiographic outcomes at 1 year[ 148 ].…”
Section: Dedicated Bifurcation Stentsmentioning
confidence: 99%